2020
DOI: 10.1101/2020.12.23.424218
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Amino Acids Promote Mitochondrial-Derived Compartment Formation in Mammalian Cells

Abstract: SUMMARYWe recently identified a new cellular structure in yeast, called the Mitochondrial-Derived Compartment (MDC), that forms on mitochondria in response to amino acid excess. While emerging evidence supports an important function for MDCs in protecting cells from metabolic stress, whether this system exists beyond yeast remains unclear. Here, we show that MDCs are conserved in mammals, and like their yeast counterparts, are responsive to the intracellular amino acid content. Specifically, we find that inhib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 70 publications
0
5
0
Order By: Relevance
“…Swelling of mitochondria, in turn, may impair the action of the fission machinery. Interestingly, it was reported that, in mammalian cells, expansion of the so-called “mitochondrial derived compartment,” a newly described membranous organelle derived from the OMM, requires Miro and contacts between mitochondria and the ER, consistent with a role of Miro in a process that may involve lipid flux from the ER ( English et al, 2020 ; Schuler et al, 2020 Preprint ).…”
Section: Discussionmentioning
confidence: 91%
“…Swelling of mitochondria, in turn, may impair the action of the fission machinery. Interestingly, it was reported that, in mammalian cells, expansion of the so-called “mitochondrial derived compartment,” a newly described membranous organelle derived from the OMM, requires Miro and contacts between mitochondria and the ER, consistent with a role of Miro in a process that may involve lipid flux from the ER ( English et al, 2020 ; Schuler et al, 2020 Preprint ).…”
Section: Discussionmentioning
confidence: 91%
“…The large diameter and lack of mitochondrial matrix proteins in SPOTs suggested that they differed from fragmented mitochondria as well as mitochondria-derived compartments (MDCs) and mitochondria-derived vesicles (MDVs), which form in response to amino acid toxicity and oxidative stress, respectively (14)(15)(16)(17)(18)(19). MDCs average 1 mm in diameter and depend on the OMM guanosine triphosphatase (GTPase) MIRO1 (mitochondrial rho GTPase 1), which mediates mitochondrial trafficking (16,17).…”
Section: Mitochondria Shed Spots During Toxoplasma Infectionmentioning
confidence: 99%
“…BFP-OMP25 and mCherry- OMP25 were generated by cloning the OMP25 cassette from GFP-OMP25 into the XhoI/BamHI sites of pTagBFP-C and pmCherry-C1, respectively. TIMM50-GFP was generated by PCR amplifying the TIMM50 cassette from pLenti-mTIMM50-mRFP (a gift of Adam Hughes; (Schuler et al, 2020)) and cloning into the XhoI/BamHI sites of pAcGFP1-N1. TIMM50-mCherry was subsequently generated by digesting the mCherry cassette from pmCherry-N1 and cloning into the BamHI/NotI sites of TIMM50-GFP.…”
Section: Methodsmentioning
confidence: 99%